6n+4=-2n

Simple and best practice solution for 6n+4=-2n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6n+4=-2n equation:


Simplifying
6n + 4 = -2n

Reorder the terms:
4 + 6n = -2n

Solving
4 + 6n = -2n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '2n' to each side of the equation.
4 + 6n + 2n = -2n + 2n

Combine like terms: 6n + 2n = 8n
4 + 8n = -2n + 2n

Combine like terms: -2n + 2n = 0
4 + 8n = 0

Add '-4' to each side of the equation.
4 + -4 + 8n = 0 + -4

Combine like terms: 4 + -4 = 0
0 + 8n = 0 + -4
8n = 0 + -4

Combine like terms: 0 + -4 = -4
8n = -4

Divide each side by '8'.
n = -0.5

Simplifying
n = -0.5

See similar equations:

| (-32)+x=-18 | | 48kd=3.2k | | 6x-3+x-2=-5 | | X^2+45x-450=0 | | 4x-23/8= | | 12y+y(y-6)=4 | | 9x^2-18-2=0 | | 2(2+2n)=3(n+1) | | -110+3x=33-8x | | 5x+x=-42 | | -8=1/10z+3/10z | | 4x^6-24x^5+8x^4=0 | | 5n+3=2(n+2)+-3n | | y^2-10y-9=0 | | X+2x+3x=440 | | y=2x^2+16x+25 | | -q+9+7q=4q-9 | | 9x-4x+8=1x+20 | | -1/4+6=2/3x+28 | | 5x+2+2-2x=10 | | a=-10 | | y+7=.33333(x+2) | | X-(2x-5)=4x-(x+42) | | [-2x+22-3z]=[6x-2y+45] | | 4=3h-2 | | G-10=-9g+10 | | -2(b+3)=16 | | 3b^2-2b+16=0 | | x+(x+15)=44 | | a-2-5=0 | | 5x+12=2x+354 | | 1(1-3x)=2(-4x+7) |

Equations solver categories